The effect of deprivation on the developmental activities of adolescent rugby union players in Wales - Melitta McNarry (Journal of Sports Sciences, 2016)
The developmental activities of rugby union players and their interaction with deprivation remain to be elucidated. Five-hundred and ninety elite junior rugby union players (14.8 ± 0.5 years) were split into deprivation quintiles. These players subsequently completed a participant history questionnaire to record their involvement in rugby and other sports. Players accumulated 1987 ± 1297 h in rugby between 6 and 15 years of age. During the mini rugby stage (6–10 years of age), players accumulated an average of 113 ± 105, 89 ± 69 and 43 ± 19 h per year in rugby play, practice and competition, respectively. Moreover, 461 players engaged in an average of two other sports during the mini rugby stage. During the junior rugby stage (11–15 years of age), players accumulated 179 ± 98, 115 ± 90 and 64 ± 26 h per year in rugby practice, play and competition, respectively, and 538 players took part in three other sports. Players who were more deprived accumulated less rugby hours and participated in fewer other sports, but age milestones were not different between deprivation quintiles. There were no differences within developmental activities in rugby between deprivation groups.